Communique of the 16th ordinary Summit of the East African Community Heads of State - EAC (EAC)
Held at Kenyatta International Convention Centre. Nairobi, Kenya
Deepening and accelerating integration: Towards Political Federation
Keywords: Political Federation; Regional integration